Can simple intensification of therapy with modern two-phase insulin help in type 2 diabetes when target glycemia failed to be achieved withbasal insulin? Results of subanalysis in the PRESENT study - Ch S Yang (Endocrinology Research Centre, 2009)
Aim. To evaluate efficiency and safety of intensification of therapy by substituting two-phase insulin aspart 30 (DiAsp 30) for basal insulin in patients with type2 diabetes mellitus after a failure to achieve target glycemia. Materials and methods. Analysis of the data obtained in a group of patients involved in the PRESENT study (Physicians Routine Evaluation of Safety andEfficacy of NovoMix 30 Therapy), a 6 month-long observational study conducted in 15 countries. The subanalysis included patients previously treated with along-acting insulin analog (AB, n=34) or intermediate and long-acting human basal insulin (HB, n=3414) and transferred thereafter to DiAsp 30 therapy.End-points of efficiency were the difference between blood HbА1c and glucose (fasting and postprandial) levels measured at the onset of the study and upon itscompletion, the number of hypoglycemic episodes and adverse events, physician and patients content with the results of the treatment. End-points were consideredseparately with reference to preceding basal therapy (AB or HB). Results. Treatment with DiAsp 30 for 6 months resulted in a fall of HbА1c levels compared with initial values (-1,60 and -142% in AB and HB patients respectively,p